Are GMI gangliosidosis and Morquio type B two different disorders or part of one phenotypic spectrum?. Issue 1 (18th March 2021) - Kingma, Sandra D. K.; Ceulemans, Berten; Kenis, Sandra; Jonckheere, An I.
Abstract: Monosialotetrahexosylganglioside (GMI) gangliosidosis and Morquio type B (MorB) are two lysosomal storage disorders (LSDs) caused by the same enzyme deficiency, β‐galactosidase (βgal). GMI gangliosidosis, associated with GMI ganglioside accumulation, is a neurodegenerative condition characterized by psychomotor regression, visceromegaly, cherry red spot, and facial and skeletal abnormalities. MorB is characterized by prominent and severe skeletal deformities due to keratan sulfate (KS) accumulation. There are only a few reports on intermediate phenotypes between GMI gangliosidosis and MorB. The presentation of two new patients with this rare intermediate phenotype motivated us to review the literature, to study differences and similarities between GMI gangliosidosis and MorB, and to speculate about the possible mechanisms that may contribute to the differences in clinical presentation. In conclusion, we hypothesize that GMI gangliosidosis and MorB are part of one phenotypic spectrum of the same disease and that the classification of LSDs might need to be revised.